Diet Quality and School Attendance: Cost Analysis Informing Absence‐Reduction Strategies in Schools With Underserved Students. (29th July 2022) - Kukla‐Acevedo, Sharon A.; Ernst, Micah G.; Sommer, Evan C.; Adams, Laura E.; Barkin, Shari L.
ABSTRACT: BACKGROUND: As school districts across the nation evaluate strategies and implement programs to reduce absenteeism, health‐related interventions remain largely underutilized. This study provides the estimated cost of improving students' diet quality as a means to increase attendance. Then, it compares the costs and efficacy of improving diet quality to those of other absence‐reduction interventions. METHODS: This study used child‐level diet quality data from the Growing Right Onto Wellness (GROW) randomized control trial merged with Metro Nashville Public Schools (MNPS) absences data, as well as food cost estimates from Rose et al. to study the cost effectiveness of improving underserved elementary student attendance through improved diet quality. RESULTS: The results suggest that improving diet quality might be a cost‐efficient way of improving attendance among elementary students in underserved areas. Further, improving diet quality compares favorably to other absence‐reduction strategies, in terms of cost and effectiveness. CONCLUSIONS: Investments in school food programs to improve diet quality may be a cost‐effective strategy to reduce student absenteeism, especially for schools with higher concentrations of students with lower diet quality. These results may assist decision‐makers who allocate scarce resources aimed at improving school attendance.